Implementation and Analysis of DSRC protocol in order to prevent and avoid collision among vehicles - Kamaldeep Joshi, Devendra Kumar, Rishabh, Sunita Dhingra (International Journal of Advanced Science and Technology, 2020)
In this research paper, we tried to study different routing protocols for VANET which helps in reducing traffic, reducing accidents through efficient communication. We studied different methods in collision hindrance process that support to put off from multiple chain collisions. The proposed model helps in getting the information about vehicle and traffic during unexpected emergencies. To avoid collision an alert mail to other vehicles is being telecast for usual brake control. The model send alert messages to vehicles in the network, prior to them arrive at the danger zone. This paper focuses on many approaches that would be handy in preventing collision hindrance in vehicular ad-hoc network.